CONTRIBUTION TO THE STUDY OF FAT SEPARATION IN THE EVAPORATED CANNED MILK - ΣΚΟΥΝΤΖΟΣ Κ.; ΠΑΠΑΔΙΑ Α.; ΑΣΙΚΗΣ Ι.; ΜΟΥΤΟΥΣΙΔΗΣ Γ. (Journal of the Hellenic Veterinary Medical Society, 1973)
The authors examined the fat content of different layers of evaporated, unsweetened milk, its viscosity and the size of the contained fat droplets during predetermined time - intervals and under fixed thermal conditions. On the basis of their findings they propose various measures of improving the types of condensed, unsweetened canned milk produced in Greece.